Levantamento populacional e manejo de Quatis (PROCYONIDAE: Nasua nasua) no Parque das Mangabeiras, Belo Horizonte, MG - Nadja Simbera Hemetrio (2011)
The Mangabeiras Park (236 ha) is an urban fragment in the transition area between the Atlantic Forest and Cerrado biomes, located in the municipality of Belo Horizonte, Minas Gerais. In the year 2007, a study carried out at the site verified a high density of coatis (Nasua nasua), indicating the need of monitoring the species abundance. The capture-recapture method was employed to estimate the population of coatis in the site between the years 2008 and 2010. A total 106 coatis were captured, after a sample effort of 4.500 traps/day and with a success rate that varied from 1,13% to 6,73%. Trapping success was smaller in the periods where hook traps were used in relation to those where pedal traps were employed (t= 63,12; GL = 1; p< 0,0001). The individuals captured were divided in age classes (youngs, sub-adults, adults) according to their weight. No difference was observed in the proportion of individuals in each age class in the years studied (X²= 3,8677; GL= NA; p=0,43). The distribution of individuals was homogeneous among the age classes and this may reflect a high survival of the adults. The population presented a sex ratio of 1:1 in all age classes (p>0,05) and in all years sampled, with the exception of the sub-adults in 2010 (p=0,052). The capture history was assessed with the open population model and the estimation was possible only for the year 2010. Population size was 124 + 29,5 individuals and the recapture rate was low in 2009 and inexistent in 2008. At area effectively sampled in 2010 was 4,13 km² through the minimum polygon convex (MPC) plus a buffer area that considered the mean maximum distance moved (MMDM) by the individuals. Density was estimated at 30,03 individuals/km², which is above of what would be expected in natural conditions. Food supplementation (garbage cans contents and food offering by visitors) and the absence of predators in the site may be the causes of this high density, which I turn could result in alterations in the ecosystem. The population size must be monitored and management strategies, environmental education and waste conditioning should be employed in order to control the coatis population.